An Exploration of the Contemporary Work Ethic of IT Industry Employees in the United States - Moyers, Debra; Hild, Cheryl; Metz, Kelsey; Ray, Joshua (Journal of Applied Business and Economics, 2024)
This study contributes to the growing body of research identifying work ethic as an integral part of organizational performance. IT work in the U.S. is an essential component of the contemporary work environment as the dependency on technological resources increases. Relying on IT workers as respondents, this study examined multiple aspects of work ethic including changes in its aggregate level over time, differences across work environments, relationships with demographics, and the influence of organizational culture. Results suggest that work ethic is relatively stable over time and across demographic categories. Important relationships between work ethic and organizational culture are discussed and the relevance to the IT profession are supported.